Green synthesis and characterization of Fe3O4 nanoparticles using Chlorella-K01 extract for potential enhancement of plant growth stimulating and antifungal activity - Theint Theint Win (Nature Portfolio, 2021)
Abstract The purpose of this research was to determine the efficacy of iron oxide nanoparticles (Fe3O4-NPs) using microalgal products as a plant growth stimulant and antifungal agent. The work was conducted with the phyco-synthesis and characterization of Fe3O4-NPs using 0.1 M ferric/ferrous chloride solution (2:1 ratio; 65 °C) with aqueous extract of the green microalga Chlorella K01. Protein, carbohydrate and polyphenol contents of Chlorella K01 extract were measured. The synthesized microalgal Fe3O4-NPs made a significant contribution to the germination and vigor index of rice, maize, mustard, green grams, and watermelons. Fe3O4-NPs also exhibited antifungal activity against Fusarium oxysporum, Fusarium tricinctum, Fusarium maniliforme, Rhizoctonia solani, and Phythium sp. Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) scanning electron microscopy (SEM), transmission electron microscopy (TEM), particle size analysers (PSA), and zeta potential (ZP) measurements were used to characterize these green fabricated magnetite NPs. FTIR analysis showed that the synergy of microalgal proteins, carbohydrtates and polyphenols is responsible for the biofabrication of iron nanoparticles. A spheroid dispersion of biosynthesized Fe3O4-NPs with an average diameter of 76.5 nm was produced in the synthetic process.